Preparation method of novel multi-channel core-shell structure nano graphite silicon battery slurry
By using the preparation method of multi-channel core-shell structure nanographite silicon battery slurry in lithium-ion batteries, the ceramic ball shearing effect during sand grinding is used to solve the problem of insufficient dispersion and conductivity of graphite silicon composite materials, and the cycle stability and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510302015.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-05-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the preparation process, the graphite silicon composite materials in existing lithium-ion batteries have problems such as poor interaction between silicon and graphite, poor dispersion and insufficient conductivity, resulting in limited cyclic stability and energy density of the battery.
The preparation method of multi-channel core-shell structure nanographite silicon cell paste is adopted. Through the shearing action of ceramic balls during sand grinding, the graphite particles are dispersed evenly, and graphene quantum dots and graphite nanosheets are generated to improve conductivity and stability.
It significantly improves the dispersion, conductivity and cycle stability of the battery material, extends the cycle life of the battery, and improves the rate performance.
Smart Images

Figure CN120072905A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery anode materials, and particularly relates to a preparation method of a novel multi-channel core-shell structured nano graphite-silicon battery slurry. Background Art
[0002] With the continuous growth of energy demand and the improvement of environmental protection awareness, lithium-ion batteries, as an efficient and environmentally friendly energy storage device, are widely used in fields such as electric vehicles, mobile electronic devices, and energy storage systems. However, traditional lithium-ion batteries still face certain challenges in terms of energy density, cycle life, and safety. In order to further improve the performance of lithium-ion batteries, researchers have been continuously exploring new battery materials and optimizing battery structures. Among them, graphite-silicon composite materials are widely regarded as an effective way to improve battery performance due to their good electrical conductivity, high specific capacity, and low price.
[0003] In the preparation process of existing graphite-silicon composite materials, traditional slurry preparation methods mostly adopt a single material system, often having problems such as poor interaction between silicon and graphite, poor dispersion, and insufficient electrical conductivity, resulting in limited overall performance of the battery. Especially during the charge and discharge process of the battery, silicon is prone to expansion and fragmentation, thus affecting the cycle stability.
[0004] In recent years, core-shell structured materials have received increasing attention because they can effectively inhibit the expansion and fragmentation of the core material and significantly improve the stability and electrical conductivity of the material. In the design of the core-shell structure, the outer shell material can provide protection for the core material, and at the same time, the selection of the outer shell material can also affect all aspects of battery performance. As a novel composite material, multi-channel core-shell structured nano materials can not only improve the battery capacity while improving its electrical conductivity, stability, and cycle performance, but also are expected to provide new ideas and solutions for further improving battery performance.
[0005] Therefore, how to prepare a nano graphite-silicon slurry with good dispersion, stability, and electrical conductivity and optimize its preparation process has become an important topic in the current material field and battery technology. Summary of the Invention
[0006] The purpose of the present invention is to provide a preparation method of a novel multi-channel core-shell structured nano graphite-silicon battery slurry to solve the problems of poor dispersion and insufficient electrical conductivity of existing battery anode nano graphite-silicon composite materials, thus affecting the cycle stability and energy density of lithium-ion batteries.
[0007] The present invention realizes the above purpose through the following technical solutions: A preparation method of a novel multi-channel core-shell structured nano graphite-silicon battery slurry, comprising the following steps:
[0008] S01. Weigh the following raw materials according to parts by mass: 100 - 1000 parts of ceramic balls, 15 - 150 parts of solvent, 1 - 20 parts of graphite, 1 - 10 parts of silicon, 0.1 - 1 part of conductive agent, 0.1 - 1 part of dispersant, and 0.1 - 1 part of binder;
[0009] S02. Connect the sanding tank to the cooling water circulation to ensure that the temperature during the entire sanding process is controlled at 15 - 40 °C;
[0010] S03. Disperse the ceramic balls and graphite in the solvent and sand for 1 - 6 h to obtain a graphite suspension;
[0011] S04. Add silicon to the graphite suspension obtained in step S03, and then stir for 3 - 6 h. During the stirring process, the ceramic balls shear the graphite, and at the same time, the graphite shears and rubs against each other, so that the surface of the graphite flakes is peeled off to obtain graphene quantum dots and graphite nanosheets, and a nanosheet graphite - silicon slurry is obtained;
[0012] S05. Add the conductive agent and dispersant to the nanosheet graphite - silicon slurry obtained in step S04 and sand for 3 - 6 h to obtain a uniformly dispersed nanosheet graphite - silicon slurry;
[0013] S06. Add the binder to the nanosheet graphite - silicon slurry obtained in step S05 and sand for 0.1 - 1 h to obtain a graphite - silicon slurry in a viscous - flow state;
[0014] S07. Screen and filter the graphite - silicon slurry obtained in step S06 to obtain a graphite - silicon slurry without ceramic microspheres.
[0015] Further, in step S01, the ceramic balls are micron - sized ceramic balls, which are one or a combination of zirconia, alumina, silicon nitride, and silicon carbide micron - balls, and the diameter of the ceramic balls is 50 - 600 μm; the solvent includes one or a combination of deionized water, methanol, ethanol, isopropanol, N - methylpyrrolidone, and N,N - dimethylformamide; the graphite includes one or a combination of massive graphite, flake graphite, cryptocrystalline graphite, and artificial graphite; the particle size of silicon is 0.03 - 5 μm; the conductive agent is one or a combination of carbon black, conductive graphite, carbon fiber, carbon nanotubes, and graphene; the dispersant is one or a combination of polyvinylpyrrolidone, modified polyoxyethylene ether, tamarind gum, and carboxymethyl cellulose; the binder is one or a combination of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene - butadiene rubber, polyvinyl alcohol, polyacrylic acid, and polytetrafluoroethylene.
[0016] Further, in step S03, the viscosity of the graphite suspension is 2000 - 10000 Mpa·s.
[0017] Further, the sanding speed in the steps S03, S04, S05 and S06 is 500 rpm - 10,000 rpm.
[0018] Further, the mesh number of the sieve used in the step S07 is 50 - 300 meshes, and the suction filtration time is 1 - 10 min.
[0019] Beneficial effects: The present invention is reasonably designed, has a simple and stable structure, and strong practicability, and has the following advantages:
[0020] 1. Improvement of production process efficiency: In order to obtain graphite nanosheets and graphene quantum dots, graphite powder is first exfoliated by sanding. During the exfoliation process, small organic solvent molecules enter between the graphite layers, increasing the layer spacing of the graphite nanosheets, which helps to improve the exfoliation efficiency;
[0021] 2. Improvement of overall performance: During the sanding process of graphite nanosheets and silicon, due to intermolecular forces, the graphite nanosheets are evenly coated around the silicon. The graphite nanosheets have a high specific surface area, and adjacent graphite nanosheets carry the same charge, forming an electrostatic repulsion force. A blocked grid is formed between the graphite nanosheets, which is more conducive to alleviating the pulverization problem caused by the volume expansion of silicon, improving the cycle stability of the electrode material, and increasing the cycle life;
[0022] 3. Further optimization of performance: The selected graphite material has pores formed by some defects, which can provide a large number of channels for ion migration, improve the ion migration rate, and enhance the rate performance of the electrode material;
[0023] 4. Improvement of electrical conductivity: During the sanding process, graphene quantum dots are formed and nano graphite sheets are introduced, effectively improving the electronic conductivity, solving the problem of low conductivity of silicon, and further improving the overall conductivity of the electrode material;
[0024] 5. Broad prospects: The graphite-silicon electrode material produced by this invention has a unique multi-channel core-shell structure, and at the same time, the battery slurry is made by a one-step grinding method. Compared with the existing methods, it has a short production cycle and high production efficiency, and is more suitable for industrial mass production. At the same time, the method for preparing the electrode slurry of the present invention can also provide ideas and references for pulping in other fields, and has extremely high demonstration value. Description of the Drawings
[0025] Figure 1 It is the SEM image of the graphite of the present invention;
[0026] Figure 2 It is the SEM image after the graphite of the present invention is exfoliated by sanding;
[0027] Figure 3 It is the charge-discharge cycle diagram of the electrode sheet of the present invention;
[0028] Figure 4 is the rate performance graph of the electrode of the present invention;
[0029] Figure 5 is the SEM image of the graphite silicon of the present invention. Specific Embodiments
[0030] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0031] Embodiment 1:
[0032] Combined with Figures 1-5 shown, a preparation method of a novel multi-channel core-shell structure nano graphite silicon battery slurry includes the following steps:
[0033] S01. Raw material weighing: Accurately weigh the required raw materials according to the mass parts, including: 100 parts of ceramic balls, 15 parts of solvent, 1 part of graphite, 1 part of silicon, 0.1 part of conductive agent, 0.1 part of dispersant, and 0.1 part of binder. These raw materials can ensure excellent conductivity, dispersibility, and adhesiveness of the slurry under appropriate ratios;
[0034] S02. Connecting the sanding equipment: Connect the sanding tank with the cooling water circulation system to ensure that the temperature during the sanding process is maintained between 15°C. Temperature control is an important factor in ensuring the quality of the slurry. Excessive temperature may cause changes in the structure of nanoparticles and affect the performance of the final slurry;
[0035] S03. Preparation of the graphite suspension: Mix the ceramic balls and graphite according to the mass ratio and disperse them in the solvent. After sanding for 1 h, the graphite is fully dispersed in the solvent to obtain a uniform graphite suspension. During this process, the role of the ceramic balls is to help the graphite particles disperse and reduce aggregation through shear action, ensuring the stability of the suspension;
[0036] S04. Generation of graphene quantum dots: Add silicon to the graphite suspension and continue sanding for 3 h. The shear action of the ceramic balls at this stage not only causes the graphite particles to rub against each other but also promotes the gradual peeling of the graphite sheet surface, generating graphene quantum dots and graphite nanosheets. Finally, a nano-sheet graphite silicon slurry is obtained. The formation of graphene quantum dots and graphite nanosheets is a crucial step in the preparation process. These nano-materials can significantly improve the conductivity and electrochemical stability of the battery;
[0037] S05, adding a conductive agent and a dispersant: adding a conductive agent and a dispersant to the nanosheet graphite silicon slurry obtained in step S04, and continuing sand grinding for 3 hours. The addition of the conductive agent helps to improve the conductivity of the battery, and the dispersant can further improve the dispersibility of the slurry, prevent the agglomeration and sedimentation of the particles, and ensure the uniformity and stability of the slurry;
[0038] S06, adding a binder: adding a binder to the slurry obtained in step S05, and sanding for 0.1 h until the slurry presents an appropriate viscous flow state. The binder is added to ensure that the slurry can be well combined with the electrode material during the coating process and play a stabilizing role in the subsequent battery assembly;
[0039] S07, screening and filtration: Finally, the obtained graphite silicon slurry is screened and filtered to remove the ceramic microspheres therein, and obtain pure graphite silicon slurry without ceramic balls. This step ensures that the slurry does not contain impurities that affect battery performance, thereby improving the quality of the final product.
[0040] Through the above steps, the present invention successfully prepares a nano-graphite silicon battery slurry with a novel multi-channel core-shell structure. The slurry has excellent dispersibility, conductivity and adhesion, and is suitable for the manufacture of high-performance batteries.
[0041] Among them, in step S01, micron-sized ceramic balls are used as grinding media, and their materials include various materials such as zirconium oxide, aluminum oxide, silicon nitride and silicon carbide micron balls, or a combination of these materials. The diameter of the ceramic balls ranges from 50 to 600 μm, and can be adjusted according to different application requirements to obtain the best grinding effect. Zirconia ceramic balls have excellent wear resistance and chemical stability, and are suitable for high-precision grinding and dispersion operations; aluminum oxide ceramic balls have good cost-effectiveness and are widely used in grinding processes with lower requirements. Silicon nitride and silicon carbide ceramic balls have extremely high hardness and are suitable for high-intensity material processing, especially for applications requiring high durability and low wear.
[0042] The choice of solvent is crucial to the dispersion and dissolution process. In this process, the solvents include deionized water, methanol, ethanol, isopropanol, N-methylpyrrolidone and N,N-dimethylformamide. Each solvent or its combination has different solubility and polarity characteristics, which can effectively improve the dispersibility, stability and fluidity of the raw materials. Deionized water is used to treat water-soluble substances and has low chemical reactivity. Methanol and ethanol perform well in organic dissolution and dispersion. Isopropanol, N-methylpyrrolidone and N,N-dimethylformamide are suitable for dispersing high molecular weight and insoluble substances due to their extremely high solubility and polarity.
[0043] The selection of graphite as a conductive material is crucial. Various types can be used, such as massive graphite, flake graphite, cryptocrystalline graphite, and artificial graphite, or combinations of these materials. Massive graphite has larger particles and stronger conductivity. Flake graphite can provide better conductivity and lubricity due to its layered structure. Cryptocrystalline graphite can offer more uniform conductivity performance and is suitable for high-precision applications. Artificial graphite has good formability and controllable conductive characteristics and is widely used in fields requiring high consistency.
[0044] The particle size range of silicon is 0.03 - 5 μm. It is used in many high-performance materials to improve strength and thermal stability. Silicon has a large specific surface area and can improve the conductivity, thermal conductivity, and electrochemical performance of materials while enhancing their strength.
[0045] The selection of conductive agents is crucial for the conductivity performance of battery materials. Conductive agents include carbon black, conductive graphite, carbon fiber, carbon nanotubes, and graphene. These conductive materials or their combinations can significantly improve the conductivity of materials, thereby enhancing the overall performance of the battery. Carbon black is widely used due to its good conductivity and dispersibility. Conductive graphite provides excellent conductivity and chemical stability. Carbon fiber, carbon nanotubes, and graphene have extremely high specific surface areas and excellent conductivity, which can greatly enhance the conductive performance of materials and play an important role especially in high-power battery applications.
[0046] The role of dispersants in this process is to optimize the dispersion effect of materials and prevent agglomeration and precipitation. They include polyvinylpyrrolidone, modified polyoxyethylene ether, tamarind gum, and carboxymethyl cellulose. Polyvinylpyrrolidone has good dispersion ability and viscosity adjustment performance. Modified polyoxyethylene ether can play a stabilizing role during dispersion to prevent material aggregation. Tamarind gum and carboxymethyl cellulose, as natural polymers, have good biocompatibility and dispersion performance and are suitable for the manufacture of green and environmentally friendly products.
[0047] Binders are important materials to ensure the stability and mechanical strength of the final product. Binders include polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, polyacrylic acid, and polytetrafluoroethylene. Polyvinylidene fluoride has excellent chemical stability and good electrical insulation performance and is suitable for high-demand battery materials. Sodium carboxymethyl cellulose is commonly used in aqueous systems to provide good adhesiveness and stability. Styrene-butadiene rubber and polyvinyl alcohol have good adhesiveness and film-forming properties. Polytetrafluoroethylene, as a high-performance binder, has excellent chemical and thermal stability and is suitable for high-temperature and high-humidity environments.
[0048] By optimizing the selection and combination of these materials, the performance of the final product can be significantly improved, including enhancing its conductivity, stability, mechanical strength, and durability, thereby meeting the strict requirements in different application scenarios.
[0049] Among them, in step S03, the viscosity range of the graphite suspension is 2000 - 10000 Mpa·s. This viscosity value indicates that the suspension has high rheological properties. Within this viscosity range, the graphite particles are relatively stable in the liquid medium, effectively avoiding sedimentation or stratification phenomena. This is because the higher viscosity provides stronger internal friction, inhibiting the movement and gravitational action of the particles. This range of viscosity is usually applicable to applications that require good dispersibility and stability, ensuring the uniform distribution of graphite particles in the suspension. It should be noted that too high a viscosity may increase the energy consumption in subsequent processing, such as during the stirring process. Therefore, during operation, the viscosity needs to be adjusted according to the actual process requirements to achieve the best operation effect and fluidity.
[0050] Among them, the sanding speed in steps S03, S04, S05, and S06 is 500 rpm - 10000 rpm. The specific speed selected will be adjusted according to different requirements of the production process. This range of settings is designed to ensure that the stirring process can fully mix the materials, while avoiding excessive shear or material loss that may be caused by too high a rotation speed. The lower rotation speed of 500 rpm is suitable for scenarios that require relatively gentle mixing, effectively avoiding the damage of materials and temperature rise. The higher rotation speed of 10000 rpm is suitable for situations that require strong stirring and efficient mass transfer, which can accelerate the dissolution, reaction, or dispersion process. The change in the stirring speed in different steps reflects the precise control of material processing, ensuring that the mixing effect of the materials reaches the optimum in different process stages.
[0051] Among them, the mesh number of the sieve used in step S07 is 50 - 300 meshes, and the suction filtration time is 1 - 10 min. The choice of the mesh number of the sieve directly affects the filtration effect and filtration speed of solid particles. The sieve with 50 meshes has a larger pore size and is suitable for filtering larger particles, while the sieve with 300 meshes has a smaller pore size and can effectively remove fine particles, ensuring the purity of the final product. According to different materials and filtration requirements, the mesh number of the sieve can be appropriately adjusted to balance the relationship between filtration accuracy and filtration speed. The time range of 1 to 10 min not only ensures a sufficient filtration process but also avoids material loss or over-filtration caused by too long a suction filtration time. The reasonable combination of the mesh number of the sieve and the suction filtration time ensures the efficient separation of materials, optimizes the entire process flow, and improves production efficiency and filtration effect.
[0052] Example Two:
[0053] A preparation method of a novel multi-channel core-shell structure nano-graphite silicon battery slurry, comprising the following steps:
[0054] S01. Raw material weighing: Accurately weigh the required raw materials according to the mass parts, including: 500 parts of ceramic balls, 60 parts of solvent, 10 parts of graphite, 5 parts of silicon, 0.5 part of conductive agent, 0.5 part of dispersant, and 0.5 part of binder;
[0055] S02. Connection of sanding equipment: Connect the sanding tank with the cooling water circulation system to ensure that the temperature is maintained between 30 °C during the sanding process;
[0056] S03. Preparation of graphite suspension: Mix ceramic balls and graphite according to the mass ratio, disperse them in the solvent, and sand for 4 h to fully disperse the graphite in the solvent to obtain a uniform graphite suspension;
[0057] S04. Generation of graphene quantum dots: Add silicon to the graphite suspension and continue sanding for 5 h. The shearing action of the ceramic balls at this stage not only causes the graphite particles to rub against each other, but also promotes the gradual peeling of the graphite sheet surface to generate graphene quantum dots and graphite nanosheets, and finally obtain a nanosheet graphite-silicon slurry;
[0058] S05. Addition of conductive agent and dispersant: Add the conductive agent and dispersant to the nanosheet graphite-silicon slurry obtained in step S04, and continue sanding for 5 h;
[0059] S06. Addition of binder: Add the binder to the slurry obtained in step S05 and sand for 0.3 h until the slurry shows an appropriate viscous flow state;
[0060] S07. Sieving and suction filtration: Finally, sieve and suction filter the obtained graphite-silicon slurry to remove the ceramic microspheres therein to obtain a pure graphite-silicon slurry without ceramic balls.
[0061] Example 3:
[0062] A preparation method of a novel multi-channel core-shell structure nano graphite-silicon battery slurry, comprising the following steps:
[0063] S01. Raw material weighing: Accurately weigh the required raw materials according to the mass parts, including: 1000 parts of ceramic balls, 150 parts of solvent, 20 parts of graphite, 10 parts of silicon, 1 part of conductive agent, 1 part of dispersant, and 1 part of binder;
[0064] S02. Connection of sanding equipment: Connect the sanding tank with the cooling water circulation system to ensure that the temperature is maintained between 45 °C during the sanding process;
[0065] S03. Preparation of ink suspension: Mix ceramic balls and graphite according to the mass ratio, disperse them in the solvent, and sand for 6 h to fully disperse the graphite in the solvent to obtain a uniform graphite suspension;
[0066] S04. Generation of Graphene Quantum Dots: Silicon is added to the graphite suspension, and sand grinding is continued for 6 h. The shearing action of the ceramic balls at this stage not only causes the graphite particles to rub against each other, but also promotes the gradual peeling of the graphite sheet surface, generating graphene quantum dots and graphite nanosheets, and finally obtaining a nano-sheet graphite-silicon slurry;
[0067] S05. Addition of Conductive Agent and Dispersant: A conductive agent and a dispersant are added to the nano-sheet graphite-silicon slurry obtained in step S04, and sand grinding is continued for 6 h;
[0068] S06. Addition of Binder: A binder is added to the slurry obtained in step S05, and sand grinding is carried out for 1 h until the slurry presents an appropriate viscous flow state;
[0069] S07. Sieving and Filtration: Finally, the obtained graphite-silicon slurry is sieved and filtered to remove the ceramic microspheres therein, and a pure graphite-silicon slurry without ceramic balls is obtained.
[0070] Example 4: Comparison of Specific Parameter Performances of Examples 1 to 3
[0071] The specific results are as follows in the table:
[0072] Parameter Example 1 Example 2 Example 3 Raw material weighing 100 parts of ceramic balls, 15 parts of solvent, 1 part of graphite, 1 part of silicon, 0.1 part of conductive agent, 0.1 part of dispersant, 0.1 part of binder 500 parts of ceramic balls, 60 parts of solvent, 10 parts of graphite, 5 parts of silicon, 0.5 part of conductive agent, 0.5 part of dispersant, 0.5 part of binder 1000 parts of ceramic balls, 150 parts of solvent, 20 parts of graphite, 10 parts of silicon, 1 part of conductive agent, 1 part of dispersant, 1 part of binder Temperature of sanding equipment 15℃ 30℃ 45℃ Sanding time 1 h for graphite dispersion, 3 h for graphene quantum dot generation, 3 h for adding conductive agent and dispersant, 0.1 h for adding binder 4 h for graphite dispersion, 5 h for graphene quantum dot generation, 5 h for adding conductive agent and dispersant, 0.3 h for adding binder 6 h for graphite dispersion, 6 h for graphene quantum dot generation, 6 h for adding conductive agent and dispersant, 1 h for adding binder Sieving and suction filtration Removing ceramic balls by sieving and suction filtration Removing ceramic balls by sieving and suction filtration Removing ceramic balls by sieving and suction filtration
[0073] Analysis and Discussion from the Above Table:
[0074] 1. Analysis of Raw Material Ratio:
[0075] Ceramic Balls: As the proportion of raw materials increases, the number of ceramic balls gradually increases. From Example 1 to Example 3, the numbers of ceramic balls are 100 parts, 500 parts, and 1000 parts respectively. The role of the ceramic balls is to provide shear force to help disperse the graphite particles and contribute to the formation of graphene quantum dots. Increasing the number of ceramic balls may help improve the uniformity and stability of the slurry.
[0076] Solvent: The amount of the solvent also increases with the increase of the examples, from 15 parts to 150 parts. The increase of the solvent helps improve the fluidity and dispersibility of the slurry and reduces the aggregation between particles.
[0077] Graphite and Silicon: The ratio of graphite and silicon increases with the increase of the examples. Graphite is the main component of the battery material, while silicon plays a role in enhancing conductivity and electrochemical performance. A higher ratio of graphite to silicon is beneficial to improving the energy density and stability of the battery.
[0078] 2. Sand Grinding Process:
[0079] Sand grinding time: The sand grinding time in Example 1 is relatively short, which are 1 h for graphite dispersion, 3 h for graphene quantum dot generation, and 3 h for adding conductive agent and dispersant respectively. While the sand grinding time in Example 2 and Example 3 gradually increases. Especially in Example 3, all the sand grinding time reaches 6 h, and the time for each step is relatively long. This indicates that Example 3 has more sufficient dispersion and reaction time, which may lead to better slurry quality.
[0080] Temperature control: The temperature in Example 1 is controlled at 15 °C, which is relatively low. While the temperature in Example 2 and Example 3 gradually increases. The increase in temperature helps to accelerate the reaction rate, but it should also be noted that too high temperature may affect the stability of silicon and the formation of graphene quantum dots.
[0081] 3. Use of binder and conductive agent:
[0082] Conductive agent and dispersant: As the examples increase, the proportion of conductive agent and dispersant gradually increases. The conductive agent in Example 1 is 0.1 part and the dispersant is 0.1 part, while in Example 3 it is 1 part. This shows that with the increase in batch size, more conductive agent and dispersant are needed to maintain the conductivity and dispersibility of the slurry.
[0083] Binder: The addition amount of the binder also gradually increases, from 0.1 part to 1 part. This is to ensure that the slurry can be well combined with the electrode material during battery manufacturing and maintain a stable structure.
[0084] 4. Sieving and suction filtration:
[0085] All examples are subjected to sieving and suction filtration operations to remove ceramic microspheres and ensure the purity of the slurry. This step is to improve the quality of the slurry and reduce the negative impact on battery performance.
[0086] Summary:
[0087] The raw material ratio and sand grinding time in Example 1 are relatively short, which is suitable for small-scale production, but may be slightly inferior in terms of slurry uniformity and stability.
[0088] The raw material amount and sand grinding time in Example 2 and Example 3 gradually increase. Especially in Example 3, it may perform better in terms of slurry uniformity, stability and battery performance.
[0089] With the gradual increase of raw materials such as ceramic balls, solvents, graphite, silicon, conductive agents, dispersants and binders, the dispersibility, conductivity and adhesiveness of the slurry also improve. Therefore, the slurry quality in Example 3 may be the best and is suitable for the manufacture of large-scale and high-performance batteries.
[0090] Combining this table helps to clearly compare the key parameters between different embodiments, facilitating the analysis of their application potential in battery slurries. According to specific application requirements, a suitable embodiment can be selected for further optimization and adjustment.
[0091] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above-described exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, in any aspect, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be encompassed within the present invention. Any reference signs in the claims should not be construed as limiting the claimed invention.
[0092] In addition, it should be understood that although this specification is described in terms of embodiments, not every embodiment contains only one independent technical solution. This narrative manner of the specification is only for clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for preparing a novel multi-channel core-shell structure nanographite silicon battery slurry, characterized in that , including the following steps: S01. Weigh the following raw materials according to mass fractions: 100-1000 parts of ceramic balls, 15-150 parts of solvents, 1-20 parts of graphite, 1-10 parts of silicon, 0.1-1 parts of conductive agents, 0.1-1 parts of dispersants, and 0.1-1 parts of binders; S02, connect the grinding tank to the cooling water circulation to ensure that the temperature of the entire grinding process is controlled at 15-40°C; S03, dispersing ceramic balls and graphite in a solvent, and sand milling for 1-6 hours to obtain a graphite suspension; S04, adding silicon to the graphite suspension obtained in step S03, and then sand-milling for 3-6 hours, wherein the ceramic balls shear the graphite and cause the graphites to shear and rub against each other, thereby exfoliating the surface of the graphite sheets to obtain graphene quantum dots and graphite nanosheets, and obtaining nanosheet graphite silicon slurry; S05, adding a conductive agent and a dispersant to the nanosheet graphite silicon slurry obtained in step S04, and sand-milling for 3-6 hours to obtain a uniformly dispersed nanosheet graphite silicon slurry; S06, adding a binder to the nanosheet graphite silicon slurry obtained in step S05, and sand-milling for 0.1-1h to obtain a graphite silicon slurry in a viscous flow state; S07, sieving and filtering the graphite silicon slurry obtained in step S06 to obtain graphite silicon slurry without ceramic microspheres.
2. The method for preparing a novel multi-channel core-shell structure nanographite silicon battery slurry according to claim 1, characterized in that: In the step S01, the ceramic balls are micron-sized ceramic balls, which are one or more combinations of zirconium oxide, aluminum oxide, silicon nitride and silicon carbide micron balls, and the diameter of the ceramic balls is 50-600μm; the solvent includes one or more combinations of deionized water, methanol, ethanol, isopropanol, N-methylpyrrolidone and N,N-dimethylformamide; the graphite includes one or more combinations of block graphite, flake graphite, cryptocrystalline graphite and artificial graphite; the particle size of silicon is 0.03-5μm; the conductive agent is one or more combinations of carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene; the dispersant is one or more combinations of polyvinyl pyrrolidone, modified polyoxyethylene ether, tamarind gum and carboxymethyl cellulose; the binder is one or more combinations of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, polyacrylic acid and polytetrafluoroethylene.
3. The method for preparing a novel multi-channel core-shell structure nanographite silicon battery slurry according to claim 2, characterized in that: The viscosity of the graphite suspension in step S03 is 2000-10000 Mpa·s.
4. The method for preparing a novel multi-channel core-shell structure nanographite silicon battery slurry according to claim 3, characterized in that: The stirring speed in step S03, step S04, step S05 and step S06 is 500 rpm-10000 rpm.
5. The method for preparing a novel multi-channel core-shell structure nanographite silicon battery slurry according to claim 4, characterized in that: The mesh size of the sieve used in step S07 is 50-300 meshes, and the filtration time is 1-10 min.